INTERACTION BETWEEN LOCAL GOVERNMENT BODIES AND PUBLIC ASSOCIATIONS IN THE FIELD OF CIVIL PROTECTION: LEGAL MECHANISMS AND IMPLEMENTATION PRACTICE - Vasylenko, O.; Kletskovskyy, I. (Public administration and state security aspects, 2025)
The article is devoted to the study of international legal foundations for providing humanitarian assistance to victims of natural disasters and man-made catastrophes in the context of reforming Ukraine's civil protection system. The evolution of international cooperation in the field of disaster prevention and emergency assistance to victims has been analyzed. Special attention is paid to the formation of the right to receive humanitarian assistance as a component of international customary law in conditions of war and post-conflict recovery. The principles of international cooperation in the field of environmental protection and prevention of transboundary disasters are examined, taking into account the specifics of martial law in Ukraine. The experience of international organizations, particularly the UN and EU, in coordinating humanitarian operations under conditions of armed conflict has been studied. Challenges for national civil protection systems under conditions of hybrid threats and environmental risks have been analyzed. Ways to improve mechanisms for responding to humanitarian needs in Ukraine's public civil protection regulation system are proposed, taking into account European integration processes and post-conflict recovery needs.